2015
DOI: 10.1016/j.desal.2015.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a vibratory shear membrane filtration system during the treatment of magnetic ion exchange process concentrate

Abstract: The performance of a vibratory shear enhanced unit (VSEP) used to treat waste generated from a magnetic ion exchange (MIEX) process is assessed. The unit was fitted with a NF-270 membrane (97% nominal rejection of MgSO 4 ) with an internal membrane surface area of 37 m 2 . The vibration amplitude of the module was set at 12.7mm. The system removes greater than 97% dissolved organic carbon as well as 70-85 % multivalent solutes (Mg 2+ , Ca 2+ , SO 4 2-) from the MIEX waste. The permeate generated was high in sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In experiments containing both Br – and Cl – , Br – was added at 1 mol % Cl – , corresponding to molar ratios reported in brines (i.e., 0.1–1 mol %, Table S3). ,,,,,, When isolating the effect of Cl – alone, different experiments were performed with both lower-purity (i.e., ≥99.0%, 0.004 mol % Br – , Text S3 , and Figure S4) and higher-purity (99.999%) Cl – reagents as indicated in corresponding figures. When Br – was added, lower-purity Cl – was used because the trace Br – in the Cl – reagent is negligible relative to the added Br – .…”
Section: Methodsmentioning
confidence: 99%
“…In experiments containing both Br – and Cl – , Br – was added at 1 mol % Cl – , corresponding to molar ratios reported in brines (i.e., 0.1–1 mol %, Table S3). ,,,,,, When isolating the effect of Cl – alone, different experiments were performed with both lower-purity (i.e., ≥99.0%, 0.004 mol % Br – , Text S3 , and Figure S4) and higher-purity (99.999%) Cl – reagents as indicated in corresponding figures. When Br – was added, lower-purity Cl – was used because the trace Br – in the Cl – reagent is negligible relative to the added Br – .…”
Section: Methodsmentioning
confidence: 99%
“…Operation of VSEP at set permeate recoveries of 75-85% all resulted in over 98% removal of dissolved organic carbon [20]. Molecular weight distribution analysis between the feed and permeate streams showed that the average molecular weight seen in the feed is 1400-1500 Da compared to just 1000 Da in the permeate.…”
Section: Technical Performancementioning
confidence: 98%
“…This mode of operation continues until the tank level reaches its minimal threshold of 5% and the filtration ceases. The remaining contents are drained into the same waste tank and the vessel is flushed with process water prior to the next batch [20].…”
Section: Methods Of Process Operationmentioning
confidence: 99%
“…Thus, this approach is not a sustainable waste management strategy and the treatment of the brine is inevitable. In recent years, a few studies documented the possibility of the safe treatment of the IX spent brine using membrane-based techniques (mainly using nanofiltration) [ 9 , 10 ]. Nonetheless, the severe membrane NOM fouling of the nanofiltration membranes has impaired the long-term applicability of this option [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%